Investigation on formulation parameters of donepezil HCl loaded solid lipid nanoparticles - Gizem Rüya Topal; Berrin Küçüktürkmen; Umut Can Öz; Erva Özkan; Filiz Bakar-Ates; Asuman Bozkır (Universidade de São Paulo, 2023)
Abstract Donepezil-HCl is a member of the acetylcholinesterase inhibitors that is indicated for the symptomatic treatment of Alzheimer's disease (AD) and has many side effects. In this study, to reduce the side effects of Donepezil-HCl and increase the penetration of the drug through the blood-brain barrier, we aimed to design a solid lipid nanoparticle (SLN) formulation. The effects of the different formulation parameters, such as homogenization speed, sonication time, lipid and drug concentration, surfactant type and concentration, and volume of the aqueous phase, were assessed for optimization. The particle size and PDI increased with increasing lipid concentration but decreased with increasing amounts of surfactant (Tween 80) and co-surfactant (lecithin). When the homogenization rate and sonication time increased, the particle size decreased and the encapsulation efficiency increased. The optimized formulation exhibited particle size, PDI, encapsulation efficiency, and zeta potential of 87.2±0.11 nm; 0.22±0.02; 93.84±0.01 %; -17.0±0.12 mV respectively. The in vitro release investigation revealed that approximately 70% of Donepezil-HCl was cumulatively released after 24 hours. TEM analysis proved that spherical and smooth particles were obtained and formulations had no toxic effect on cells. The final optimized formulation could be a candidate for Donepezil-HCl application in Alzheimer's treatment with reduced side effects and doses for patients.